Involvement of Mitochondrial Disorders in Septic Cardiomyopathy. (22nd October 2017) - Durand, Arthur; Duburcq, Thibault; Dekeyser, Thibault; Neviere, Remi; Howsam, Michael; Favory, Raphael; Preau, Sebastien
Abstract : Sepsis is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. It remains a leading cause of death worldwide, despite the development of various therapeutic strategies. Cardiac dysfunction, also referred to as septic cardiomyopathy, is a frequent and well-described complication of sepsis and associated with worse clinical outcomes. Recent research has increased our understanding of the role of mitochondrial dysfunction in the pathophysiology of septic cardiomyopathy. The purpose of this review is to present this evidence as a coherent whole and to highlight future research directions.